2019
DOI: 10.1177/1469787419860204
|View full text |Cite
|
Sign up to set email alerts
|

A degree of studying? Approaches to learning and academic performance among student ‘consumers’

Abstract: The marketization of higher education and focus on graduate employability and earnings data has raised questions about how students perceive their roles and responsibilities while studying for their degree. Of particular concern is the extent to which students identify themselves as consumers of their higher education, for example, whether they view their degree as a purchasable commodity to improve future earnings. This is because research has found that a stronger consumer identity is related to lower academ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 36 publications
0
6
0
2
Order By: Relevance
“…As a result of these interactions, the student may take a learner or a non‐learner identity, which may include the consumer identity proposed by Bunce et al . (2017) and Bunce and Bennett (2019). Cooperation (through scaffolding or cooperative learning) will further boost student interest in the course and may foster an identity shift in those students who previously adopted a non‐learner identity (Figure 7).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…As a result of these interactions, the student may take a learner or a non‐learner identity, which may include the consumer identity proposed by Bunce et al . (2017) and Bunce and Bennett (2019). Cooperation (through scaffolding or cooperative learning) will further boost student interest in the course and may foster an identity shift in those students who previously adopted a non‐learner identity (Figure 7).…”
Section: Discussionmentioning
confidence: 98%
“…Students with a consumer identity tend to be less engaged in their studies and take surface approaches to learning. In addition, higher consumer identities have been negatively correlated with academic performance (Bunce et al ., 2017; Bunce & Bennett, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Poměrně stabilní napříč sociokulturními prostředími jsou výsledky týkající se přístupu ke studiu, tedy způsobu, jakým se studenti vyrovnávají s učivem a řešením studijních úkolů (Säljö, 1979). Až na výjimky (Barac et al, 2016) s vyšším věkem narůstá hloubkový přístup (Bunce & Bennett, 2019;Richardson, 1995;Rubin et al, 2018) vyznačující se snahou porozumět problémům a hledat souvislosti, případně přístup strategický vyznačující se dobrým porozuměním zadání a plánování řešení tak, aby student co nejlépe uspěl (Entwistle et al, 2001). Naopak povrchový přístup, u nějž dominuje memorování, s vyšším věkem klesá (Aaron & Skakun,1999;Biggs, 1987).…”
Section: Studenti Kombinovaného Studiaunclassified
“…There is emerging evidence suggesting that students’ approaches to learning are also negatively affected by the marketization of higher education, with its emphasis on extrinsic motivation for attending, such as obtaining well-paid employment ( Naidoo and Williams, 2015 ). For example, Bunce and Bennett (2021) recently showed that approaches to learning mediate the negative relation between a consumer identity and academic achievement. Specifically, they found that students who identified more strongly as consumers had lower achievement because they were less likely to adopt deep approaches to learning and more likely to adopt surface approaches.…”
Section: Introductionmentioning
confidence: 99%